2022
DOI: 10.1088/1742-6596/2190/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Drug loading ability and release study of various size small mesoporous silica nanoparticle as drug carrier

Abstract: Mesoporous silica nanoparticles (MSN) have been widely developed as drug carriers for various drug models in various particle sizes. The morphology of MSN becomes one of the factors which influence drug loading ability. In this study, we investigated the correlation between particle size and surface charge toward the loading ability of MSN. We used various morphology of MSN included its zeta potential value and quercetin as a drug model. The result showed that both particle size and zeta potential value have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…33 Increased values for the zeta-potential difference may represent drug loading. 34 The loading capacity for a drug can be influenced by the morphology of the drug carriers, including the particle size and zeta potential of nanoparticles. The interaction between medicinal compounds and nanoparticles can alter the zeta potential depending on drug loading on or in the nanoparticle.…”
Section: Resultsmentioning
confidence: 99%
“…33 Increased values for the zeta-potential difference may represent drug loading. 34 The loading capacity for a drug can be influenced by the morphology of the drug carriers, including the particle size and zeta potential of nanoparticles. The interaction between medicinal compounds and nanoparticles can alter the zeta potential depending on drug loading on or in the nanoparticle.…”
Section: Resultsmentioning
confidence: 99%
“…While the positive zeta potential of the TABP‐PDA‐COF ( ζ TABP‐PDA‐COF = 12.13 ± 1.28 mV) reduces agglomeration and enables sufficient drug loading values, the negative zeta potential of the TpAzo‐COF ( ζ TpAzo‐COF = −19.67 ± 0.68 mV) reduces drug loading due to electrostatic repulsions. [ 38 ] In addition, a lower crystallinity and thereby, possibly decreased accessible pore volume of TpAzo‐COF are expected to lead to reduced DOX uptake. Overall, the DOX uptake of both COF materials is among the highest reported, also relative to other artificial structures using physical encapsulation.…”
Section: Resultsmentioning
confidence: 99%
“…Chu and co-workers [ 72 ] have described how nanofabrication techniques have hydrophobic drug loading limitations of approximately 10%, and a report by Lestari’s group [ 73 ] analyzed differently sized silica nanoparticles at drug loadings of 8.9% and 10%. They showed that there was a controlled, pH-dependent release of quercetin from the nanoparticle system, which is consistent with the results we observed.…”
Section: Discussionmentioning
confidence: 99%